Social scenario in Dr Qasim Jalaal’s Urdu and Siraiki Poetry - Dr. Shaista Hameed Khan (Corresponding Author); Dr. Aqsa Sajid; Badar Masood Khan (Al-Qanṭara, 2024)
Dr. Syed Muhammad Qasim Jalal is one of the well known urdu, Siraiki and Punjabi poet. He also writesin fiction and in prose. But his poetry is above all. He is a keen observer of the society. He earned name and fame. He know the realities of like livings of oppressed people remain in his mind. He also experience the dying humanity among his people. He is brave and courageous people of his land are suffering and focing very hard and tough situation of life. They are facing Hunger, thrust, injustice and the contradictions of the behaviors. Qasim consoles his people and says that the day will surely come when all these hurdles shall be rooted out. Poet is from them and always stand with them hoisting the flag of happiness, Joy and Harmony. He knows that the sorrows and grief destroyed badly the innocent and poor people of his home land. He has not the power to change the cruel system but he is the leader of his community. He is like a guiding star. He provides them the directions of pleasure for them